TERMINATION TRANSFORMATION OF THE FRAGMENTARY CAPSULE AFTER A GUNSHOT - Lurin, I.A.; Makarov, V.V.; Nehoduiko, V.V.; Tertyshnyi, S.V.; Vastyanov, R.S.; Chobey, S.M.; Korol, S.O. (World of Medicine and Biology, 2023)
By the method of Mikel Calvo in the modification of Davydenko S.I. by staining the carboxyl and basic groups of proteins, it was proven that the perversion of the synthesis and maturation of the connective tissue of the periosteal capsule is due to the presence of metal fragments, soot, chemicals and elements. In the capsule around the fragment located in the dermis, in the period from 4 months to 6 years, due to contact with large and small metal fragments, disorganization of collagen occurs with a decrease in the relative number of basic amino groups of proteins and an increase in the relative number of acidic proteins due to carboxyl and hydroxyl groups. Endless destruction of maturing connective tissue fibers by carboxyl groups of proteins and their predominance over basic groups contributes to tissue acidosis and enhances metabolic proteolysis processes, destroying surrounding tissues, preventing tissue healing and leading to final fibrosis and removal.
Keywords: gunshot wound; capsule; foreign body; long-term wear